The Impact Of Russia's Invasion Of Ukraine On Capital Market Reaction In Energy Sector Companies Listed On The Idx - Mega Mustika Sari; Silvia Nirmala Dewi; Anika Sari; Janiman Janiman (Al-Makki Publisher, 2024)
This study was conducted to determine the impact of Russia's invasion of Ukraine on capital market reactions in energy sector companies listed on the Indonesia Stock Exchange. Abnormal Return and Trading Volume Activity are variables used to analyze reactions. Observations were made for 5 days before and 5 days after the invasion on February 24, 2022 using the T test and Wilcoxon Signed Ranks test with a sample of 29 companies and a total of 145 data tested. In the test results there are abnormal differences in return and trading volume activity before and after the invasion of Russia and Ukraine, this proves that market reaction to the events of the Russian invasion of Ukraine has strong information content and causes an increase in buying and selling activity which means investors respond to events that occur so that the market reacts.